Supply Chain Management of Textile Industry: A Case Study on Bangladesh - Mohammad Ali; Dr. Mamun Habib (International Journal of Supply Chain Management, 2012)
This study addresses a descriptive study on the current scenario of Textile industry in Bangladesh. This paper demonstrates above mentioned scenario in terms of supply chain management (SCM). The textile industry, an important segment in Bangladeshs manufacturing industry, play a critical role in its economic development. The textile sector fulfils almost cent percent domestic demand apart from the fulfilling the external demand of clothing and apparels to a large extent in Bangladesh. The Textile industry is a long chain including raw materials production, complement production, clothing production and so on. SCM concept is made possible as a conventional management tool for all manufactures are to strive to improve their product quality, to reduce their product and service cost and to shorten their product delivery and response time in a highly competitive market. This research developed based on the secondary data, including online databases, journals, review papers, etc. The effective SCM of textile industry include lower inventories, lower costs, higher productivity, greater productivity, greater agility shorter lead times, higher profits and greater customer loyalty. This paper encompasses the constraints of textile industry in Bangladesh, including ineffective communication, invisibility of SCM, long lead time, etc. which would unlock further research to develop this sector.